DETERMINAN AUDIT REPORT LAG: ANALISIS FINANCIAL DISTRESS, KOMPLEKSITAS OPERASI, DAN UKURAN PERUSAHAAN PADA SEKTOR CONSUMER CYCLICALS DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Karvicha Akwila; Theresia Olivia (Universitas Multimedia Nusantara, 2026)
Abstract— During the 2022 to 2024 post pandemic period, the timeliness of financial reporting influences market efficiency and investor confidence. Addressing an empirical research gap stemming from inconsistent prior findings in contemporary accounting literature, this inquiry models how audit report lag responds to shifts in financial distress, operational complexity, and asset scale among consumer cyclicals or consumer non primer corporations listed on the Indonesia Stock Exchange. The novelty of this research lies in evaluating these structural and financial determinants during the post pandemic economic recovery phase to resolve ongoing empirical debates. By processing secondary data through a quantitative causal lens, a purposive sampling method applied specific criteria including active listing status, consistent financial reporting, and the exclusive use of Rupiah currency. Consequently, a final sample of 115 enterprises was isolated from a baseline population of 163, generating a panel of 345 firm year observations. Multiple linear regression executed via the Random Effect Model in EViews 14 reveals contrasting results: while financial distress acts as a significant factor for prolonged audit report lag, both corporate size and operational complexity fail to register a significant impact. Substantively, this indicates that while advanced computerized audit mechanisms efficiently handle vast transaction volumes and multi tiered corporate networks, financial instability triggers extensive substantive verification and intensified auditor skepticism. Therefore, financial distress emerges as a key driver of audit report lag in the consumer cyclicals domain. To safeguard capital market reputation and minimize information asymmetry, vulnerable firms must prioritize early stage external auditor integration and optimize internal financial reporting controls.